Analysis Of Determinant Factors Influencing The Incidence Of Stunting In Toddlers: A Case Study In The Blora District - Murti Ani; Krisdiana Wijayanti; Kuswanto Kuswanto; Aulia Fatmayanti; Yanik Muyassaroh (Poltekkes Kemenkes Semarang, 2023)
Background: The incidence of short toddlers or commonly known as stunting is one of the nutritional problems experienced by toddlers in the world today. The expected national stunting target in 2024 is 14%. The prevalence of stunting under five in 2022 in Blora Regency is 25.8%. This study aimed to analyze the determinants of stunting in children under five years in Blora Regency. Methods: This is an analytical survey with a case-control study design. The sample consisted of 140 toddlers (1-5 years old) selected by systematic random sampling. The sample in this study was divided into two, namely the case sample and the case sample control (70 children under five in each group). The subsequent nutrient status assessment was performed using the calculation of longevity indicator by Age (PB/U) or Body Height by Age (TB/U) based on z-score according to WHO. Chi-square and multivariable logistic regression were used to analyze. Results: Bivariate analysis showed that exclusive breastfeeding (p=0.000), the condition of the floor of the house (p=0.000), clean water sources (p=0.000), smoking family (p=0.000), family income (p=0.000), and meat/fish/egg consumption patterns everyday (p=0.000) have a significant relationship with the occurrence of stunting in toddlers. Meat/fish/egg consumption patterns everyday of toodlers was the most dominant risk factor, among the variables. The children (1-5 years old) who never consume meat/fish/eggs every day had 4.410 times the risk of experiencing stunting (95% CI = 1.372-14.177). Conclusion: Consumption of protein (meat/eggs/fish) every day is very necessary for toddlers to prevent risk factors for stunting.